'It's all about student accessibility. No one ever talks about teacher accessibility': Examining ableist expectations in academia. Issue 7 (7th June 2022) - Saltes, Natasha
ABSTRACT: Drawing from perspectives in critical disability studies, this article examines the teaching experiences of 9 disabled graduate students in Canada and the United States. Participants took between 2 and 6 photographs that illustrated their experience teaching with a disability. Follow-up interviews were conducted to gather descriptive accounts of the meaning and significance of the photos. Thematic analysis was used to analyse the data and uncover the core themes of mobility, disclosure and teaching performance, accommodation, and careers goals. The findings shed new light on the barriers that graduate students with disabilities face navigating the dual role of learners and teachers. Data reveal that there are overt and tacit ableist expectations in academia about how those in a teaching role perform and carry out their duties. Participants in this study internalised these ableist expectations and believed that an academic career was an unlikely career option.